3D numerical analysis of atmospheric-aerosol/carbon-black nanofluid flow within a solar air heater located in Shiraz, Iran. Issue 4 (11th October 2018) - Sadripour, Soroush
Abstract : Purpose: In this study, the effects of using corrugated absorber plate (instead of flat plate) and also using aerosol/carbon-black nanofluid (instead of air) on heat transfer and turbulent flow characteristics in solar collectors were numerically investigated. Design/methodology/approach: The 3D continuity, momentum and energy equation were solved by finite volume and SIMPLE algorithm. As a result, the corrugated absorber plate was inspected in the case of triangle, rectangle and sinuous with the wave length of 1 mm and wave amplitude of 3 mm in turbulent flow regime and Reynolds number between 2, 500 and 4, 000. Choosing the proper geometry was carried out based on the best performance evaluation criteria (PEC) and increasing the air temperature from collector inlet to outlet. Findings: The results revealed that for all times of the year the highest PEC was obtained for corrugated Sinusoidal model; however, the highest temperature increase from inlet to outlet was obtained for rectangular corrugated model. In addition, the results indicated that in sinusoidal model, the nanoparticles volume fractions increase leads to heat performance coefficient increase and the best heat performance conditions were attained in volume fraction of 0.1 per cent and Reynolds number of 4, 000 for both six months period. In model with rectangular corrugated plate, usage of nanofluid in all range of Reynolds numbers leads to reduction of outlet temperature. Originality/value: The effect of some nanoparticles on heat transfer using thermal– hydraulic performances in heat exchangers has been assessed, but the effects of atmospheric aerosol-based nanofluid using carbon-black nanoparticles (CBNPs) on the heat transfer in corrugated heat sink solar collectors by 3D numerical modeling has not been yet investigated. In present study, usage of CBNPs with different volume fractions in range of 0 to 0.1 per cent in turbulent regime of fluid flow is analyzed. Furthermore, in this paper, besides the effects of using CBNPs, a solar absorber located in Shiraz, as one of the best solar irradiation receiver cities in Iran is evaluated.